2020
DOI: 10.1038/s41419-020-2305-7
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled kisspeptin receptor induces metabolic reprograming and tumorigenesis in estrogen receptor-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is a highly metastatic and deadly disease. TNBC tumors lack estrogen receptor (ERα), progesterone receptor (PR), and HER2 (ErbB2) and exhibit increased glutamine metabolism, a requirement for tumor growth. The G protein-coupled kisspeptin receptor (KISS1R) is highly expressed in patient TNBC tumors and promotes malignant transformation of breast epithelial cells. This study found that TNBC patients displayed elevated plasma kisspeptin levels compared with healthy subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Immunohistochemical analysis revealed enriched KISS1R expression localized to the plasma membrane and cytosol in human NAFL and NASH liver samples, compared with that in healthy liver ( Figure 12C ). Next, plasma KP levels were examined in male patients with NAFL and/or NASH, compared with healthy participants, as previously described ( 69 , 70 ). Because the prevalence of NAFLD parallels the rise of T2D, plasma KP levels were also examined in patients with T2D.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunohistochemical analysis revealed enriched KISS1R expression localized to the plasma membrane and cytosol in human NAFL and NASH liver samples, compared with that in healthy liver ( Figure 12C ). Next, plasma KP levels were examined in male patients with NAFL and/or NASH, compared with healthy participants, as previously described ( 69 , 70 ). Because the prevalence of NAFLD parallels the rise of T2D, plasma KP levels were also examined in patients with T2D.…”
Section: Resultsmentioning
confidence: 99%
“…However, KISS1R signaling in cancer appears to be context specific. Our earlier work has shown that, in triple-negative breast cancer (TNBC), KISS1R signaling promotes tumor growth and metastasis ( 70 ). When ERα is reexpressed in TNBC cells, KISS1R is downregulated, demonstrating that ERα negatively regulates KISS1R expression in TNBC ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Membranes were blocked for 2 h at room temperature in Blotto (5% milk in Tris-buffered saline). The membranes were incubated with an anti-AMH mouse monoclonal antibody (sc-365643) [22] (1:100 dilution; Santa Cruz Biotechnology, Inc., Dallas, TX), anti-AMHR2 rabbit polyclonal antibody (ab 197148) (1:1,000 dilution; Abcam, Cambridge, UK), anti-kisspeptin rabbit polyclonal antibody (ab 19028) [23] (1:100 dilution; Abcam), or anti-Kiss-1R rabbit polyclonal antibody (ab 137483) [24] (1:500 dilution; Abcam) in Blotto overnight at 4°C and washed for 10 min three times with Tris-buffered saline/1% Tween. A subsequent incubation with horseradish peroxidase (HRP)-conjugated secondary antibodies (anti-mouse antibody, 1:15,000 dilution; anti-rabbit antibody, 1:20,000 dilution) was performed for 1 h at room temperature in Blotto, and additional washes were performed as needed.…”
Section: Western Blot Analysismentioning
confidence: 99%